Preparation and characterization of leukocyte- and platelet-rich fibrin membrane derived from cats' blood - Castilho, Maíra Sales [UNESP]; Rahal, Sheila Canevese [UNESP]; Dias Neto, Ramiro das Neves [UNESP]; Pereira, Ana Cristina; Francia, Camila Contin Diniz de Almeida [UNESP]; Mesquita, Luciane dos Reis [UNESP]; Antunes, Carina Bueno; Lainetti, Patrícia de Faria [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (Wiley, 2021)
Autologous platelet concentrates have been used in regenerative medicine in humans due to the abundance of growth factors, but there are only a few reports in small animals. This study aimed to prepare and characterize a leukocyte and platelet-rich fibrin membrane (L-PRF) produced with blood obtained from cats. Thirteen client-owned healthy adult Maine Coon cats were enrolled. The blood samples were collected and centrifuged at 650g for 12 min using a centrifuge specifically designed for this application. The L-PRF clot was removed from the tube and red blood cell base layer was separated, leaving buffy coat intact. After this, L-PRF clot was compressed by specialized metal plate for 30–60 s, and L-PRF membrane was obtained. Light microscopy examination of the membranes showed three distinct layers: white part, buffy coat, and red part. Immunohistochemical analysis demonstrated expression of vascular endothelial growth factor and platelet derived growth factor. The scanning electron microscopy showed that three-dimensional architecture of fibrin network was more compact in the area near the buffy coat. In conclusion, the method used allowed the characterization of the L-PRF membrane composition, which presented cell types and fibrin network architecture similar to those described in the human species.
Keywords: electron microscopy; fibrin membrane; histology; immunohistochemical; L-PRF; platelet